Snus use and risk of schizophrenia and non-affective psychosis. (1st July 2016) - Munafò, Marcus R.; Larsson Lönn, Sara; Sundquist, Jan; Sundquist, Kristina; Kendler, Kenneth
Highlights: Emerging evidence suggests tobacco use may be a risk factor for psychotic illness. We observed an association between smokeless tobacco use and non-affective psychosis. This provides further evidence that tobacco may increase risk of psychotic illness. Any causal effect of tobacco use may not be due to combustion products of tobacco. Abstract: Background: Recent studies suggest a possible causal role for smoking in schizophrenia and psychosis. Most studies have focused on cigarette smoking, the most common form of tobacco use, but other forms of tobacco exist, including smokeless products such as Swedish snuff (or "snus"). Methods: We explored whether snus use is associated with schizophrenia and non-affective psychotic illness in a large Swedish registry data set. The majority of participants were aged 18 or 19 at the time of assessment. Results: We observed a positive association between snus use and odds of schizophrenia in all analyses, but the magnitude of the association was small and the confidence interval wide, consistent with no association (fully adjusted HR 1.03, 95% 0.70–1.54). A similar pattern was observed for non-affective psychosis, but the magnitude of the association was somewhat greater and the confidence intervals narrower, so that these analyses provided stronger statistical evidence for this association (fully adjusted HR 1.22, 95% CI, 1.00–1.48). Conclusions: Our results therefore provide modest evidence for an association between snus use and risk for non-affective psychosis. This is consistent with emerging evidence from a range of studies and methodologies that tobacco use may be a risk factor for psychotic illness. However, our results provide some evidence against the hypothesis that it is the burnt products of cigarette smoke that are psychotogenic.